2019
DOI: 10.3126/jsan.v6i1.24299
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes during orotracheal intubation using Airtraq video laryngoscope and direct laryngoscope: A randomized comparative study

Abstract: Introduction: Direct laryngoscopy is associated with sympathetic stimulation and altered hemodynamics. A long intubation time may result in a greater in stress response. Alternative techniques using video laryngoscopes have been developed that do not require direct vocal cord visualization and may decrease the hemodynamic response. This study aimed to compare the difference between hemodynamic changes and intubation time with Airtraq video laryngoscope and conventionl Macintosh direct laryngoscope. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Both groups were comparable and none of the p value was significant. Upadhyaya S [9] conducted a randomized comparative study on Hemodynamic changes during orotracheal intubation using Airtraq video laryngoscope and direct laryngoscope and found that Blood pressures were similar in both the groups at all times of intubation similar to our study. As per our study there is no difference in haemodynamic parameters in both the groups.…”
Section: Discussionsupporting
confidence: 85%
“…Both groups were comparable and none of the p value was significant. Upadhyaya S [9] conducted a randomized comparative study on Hemodynamic changes during orotracheal intubation using Airtraq video laryngoscope and direct laryngoscope and found that Blood pressures were similar in both the groups at all times of intubation similar to our study. As per our study there is no difference in haemodynamic parameters in both the groups.…”
Section: Discussionsupporting
confidence: 85%
“…ET intubation is aided by a metal stylet (11) . Since introduction of modern anesthesia technique, many studies have been conducted on hemodynamic changes following endotracheal intubation comparing videolaryngoscope to conventional type with different results (12,13) .…”
Section: Introductionmentioning
confidence: 99%